Prevalence and comorbidities of bronchiolitis in adults: A population-based study in South Korea. Issue 25 (24th June 2022) - Jeong, Jae Seok; Kim, Jong Seung; Yeom, Sang Woo; Lee, Min Gyu; You, Yeon Seok; Lee, Yong Chul
Abstract : Abstract: Bronchiolitis generally refers to inflammation and/or fibrosis of the non-cartilaginous small airways located approximately from the 8th airway generation down to the terminal and respiratory bronchioles. In contrast to young children, the frequency of small airway infection in adult bronchiolitis appears less frequent and a number of other pathophysiological conditions have been implicated in adult bronchiolitis. However, little information is available on the exact medical burden of bronchiolitis such as its prevalence and comorbidities in the adult population. The aim of this study is to elucidate the prevalence and comorbidities of bronchiolitis. We used the Korea National Health Insurance Service-National Sample Cohort, which provides data for 1, 000, 000 individuals out of the entire population by 2% stratified random sampling according to age, sex, residential area, and level of household income. We defined the cause of bronchiolitis other than acute infection as a patient with diagnostic code J448 or J684 and over 20 years of age who visited a clinic or hospital in South Korea. Then, 1:1 propensity score matching was performed to define a non-bronchiolitis (control) group to compare the comorbidities and mortality in the 2 groups. The overall prevalence of bronchiolitis was 688 cases/1, 000, 000 population during the study period (95% confidence interval, 625–751). The most common comorbid clinical condition in adults with bronchiolitis was rhinitis (52.3%), followed by bronchial asthma (52.23%), hypertension (43.69%), gastroesophageal reflux disease (30.56%), sinusitis (28.72%), diabetes (22.77%), and osteoporosis (17.85%). Other common bronchiolitis-associated comorbidities were cerebrovascular disease (16.86%), angina (14.37%), peripheral vascular disease (13.42%), congestive heart failure (11.9%), and malignancy in any organ (10.6%). Healthcare costs for bronchiolitis increased steeply during the same period. Malignancy in any organ was the leading cause of mortality in the patient group, followed by bronchiolitis itself. Further larger prospective multiethnic cohort studies should be carried out in the near future.